Pembelajaran Qawaid: Perspektif Teori Kognitif pada Pondok Pesantren Raudhatut Thalibin Kalimantan Selatan - Zam Zam Rasyidi (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2020)
This study aims to know the Qawa'id learning process from the perspective of Cognitive Theory at the Raudhatut Thalibin Islamic boarding school in the village of Tayur Hulu Sungai Utara (HSU) of South Kalimantan, Indonesia and to know the Qawa'id learning method with the Cognitive Theory perspective in the boarding school. This type of study is descriptive qualitative one. Data are collected through interview, observation, and documentation. The collected data was analyzed by means of the interactive model (interactive model) of Miles and Huberman. The results of this study reveal that the steps of Qowaid learning in the perspective of cognitive theory are as follows. (1) The teacher explains in advance the material to be taught using the deductive method. (2) The teacher gives examples of what has been explained before. (3) The teacher asks the students to memorize qowaid and vocabulary contained in the sentences or text they are learning. (4) The teacher will not move from one rule to another before the students really understand one rule first. The Qowaid learning methods used in the perspective of cognitive theory, namely; (1) the Nahw wa Tarjamah Method (Grammar Translation), (2) the deductive method, (3) the question and answer method, (4) and the bahtsul masa'il method.